The Dish of Theseus - Shanti Morell-Hart (Semiotic Review, 2020)
In this paper, I use the semiotic, practical, and material movements of cuisine over time to address a well-worn paradox in philosophy. Incorporating perspectives on intangible heritage, I ground the paper in linguistic approaches to foodways. By taking this standpoint, we can prod at long-standing issues of typology and temporality, as well as the iterative process of foodways generally and recipes specifically. The ancient Ship of Theseus puzzle is rooted in the physicality of objects, and can invoke subsistence as substance. But food occupies a special place given that it is equal parts material and immaterial; a meal is comprised of both tangible and intangible ingredients. If recipes "move" over time into new forms and meanings, when is the dish of Theseus no longer the dish of Theseus?